Chasing the same fish: Collaborative management initiative for shared fish stocks among the ASEAN countries - Ahmad, Mohammad Zaki; Abdullah, Mohd Kamarulnizam (2014)
Overexploitation and severe depletion of marine fisheries resources in Southeast Asia continue to be a source of great concern to many regional fisheries managers.The fact that ASEAN countries bordering these waters are highly depended upon marine fisheries as the main source of revenue, employment, and food security, it is crucial for them to address these fisheries problems.This is especially the case with respect to the management and conservation of commercially important shared pelagic fish stacks, particularly in the South China Sea and Celebes Sea As the spatial migratory range of these stock transcends across many politically draw maritime zones of littoral States, it is highly impossible for one State, acting independently, would be able to manage these fisheries effectively within its own national jurisdiction Perhaps the best approach in dealing with this problem is through collective management and conservation of fish stocks.Hence, this paper examines interstate cooperative arrangement for the management of shared fishery stocks among ASEAN countries.It begins by providing brief definition, biological and migratory profile of transboundary shared stocks. The second part covers existing international legal and policy framework that embraces the principle of interstate cooperation for managing such stocks.Finally, the paper provides recommendations of how ASEAN member States can address the issues and challenges of managing shared fish stocks in a more holistic and coordinated manner within the framework of interstate cooperation.